2019
DOI: 10.1002/mds.27892
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation for Freezing of Gait in Parkinson's Disease With Early Motor Complications

Abstract: Background Effects of DBS on freezing of gait and other axial signs in PD patients are unclear. Objective Secondary analysis to assess whether DBS affects these symptoms within a large randomized controlled trial comparing DBS of the STN combined with best medical treatment and best medical treatment alone in patients with early motor complications (EARLYSTIM‐trial). Methods One hundred twenty‐four patients were randomized in the stimulation group and 127 patients in the best medical treatment group. Presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 43 publications
2
36
0
2
Order By: Relevance
“…Aufgrund der limitierten medikamentösen Therapieoptionen und des Zusammenhangs mit der gestörten Vernetzung der motorischen Kontrollzentren im Gehirn [54] könnte die Tiefe Hirnstimulation (DBS) eine weitere Therapieoption sein. Die subthalamische (STN) Stimulation kann in der Tat zu einer Verbesserung des FOG führen [55,56]. Allerdings konnte diese Befund nicht von allen Autoren bestätigt werden, sodass verschiedene Variablen für die Therapie des Freezing mittels STN-DBS diskutiert wurden.…”
Section: Neuromodulationunclassified
See 1 more Smart Citation
“…Aufgrund der limitierten medikamentösen Therapieoptionen und des Zusammenhangs mit der gestörten Vernetzung der motorischen Kontrollzentren im Gehirn [54] könnte die Tiefe Hirnstimulation (DBS) eine weitere Therapieoption sein. Die subthalamische (STN) Stimulation kann in der Tat zu einer Verbesserung des FOG führen [55,56]. Allerdings konnte diese Befund nicht von allen Autoren bestätigt werden, sodass verschiedene Variablen für die Therapie des Freezing mittels STN-DBS diskutiert wurden.…”
Section: Neuromodulationunclassified
“…Dieses Ergebnis der ersten randomisierten und kontrollierten Studie wird gerade in einer multizentrischen Studie im Parallel-Gruppen-Design validiert. Auch die Subtypen des FOG, insbesondere die Motor-Fluktuations-assoziierten FOG Formen, lassen sich durch DBS verbessern [55,56]. Es ist jedoch noch offen, ob die berichteten positiven Effekte der DBS auf das FOG in Analogie zur Steigerung des dopaminergen Tonus stehen oder ob ein direkter Einfluss des Stimulationsortes auf die fehlerhafte Konnektivität für die FOG-Besserung verantwortlich ist.…”
Section: Neuromodulationunclassified
“…However, the impact of STN DBS on gait control is less consistent and can even result in deterioration of gait (Barbe et al, 2020;Collomb-Clerc & Welter, 2015). Conventional highfrequency DBS is provided continuously and is thought to attenuate beta activity (Kühn et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of FOG is a clinical challenge, and different strategies such as modification of levodopa dosage, adding catechol-O-methyltransferase inhibitors or amantadine, deep brain stimulation (DBS), apomorphine, metilphenidate, and even electroconvulsive therapy have been used to improve this phenomenon with varying outcomes [3]. DBS has shown significant improvement in gait and FOG [4] but in some PD patients can aggravate or even induce FOG and postural instability [5][6][7]. Previous case reports [8,9] and two recent studies [10,11] have found that FOG resistant to conventional oral therapy may benefit from levodopa/carbidopa intestinal gel (LCIG) infusion.…”
Section: Introductionmentioning
confidence: 99%